BOOK REVIEW The Crescent in the West: Image of the Orient in English Literature up to 1832 - Mohammad Teisir Bin Shah Goolfee (Hamdard Islamicus, 2021)
Abdur Raheem Kidwai is a Professor of English at the Aligarh Muslim University, India, and Visiting Professor Fellow, School of English, University of Leicester, UK (2006-2016). He has specialized in the study of Orientalism in English Literature. Equipped with amazing literary and writing skills, he has devoted his time to penning several articles and books, especially on the depiction of Muslims and Islam in English Literature. This book contains material from his Ph.D. thesis originally titled as Samples of the Finest Orientalism: A Study of the Orient in Lord Byron’s ‘Turkish Tales’ (Leicester, UK, 1993), for an extensive audience. The work consists of three chapters, along with a bibliography of Byron’s Oriental reading